Blockchain data analytics for dummies - Solomon, Michael 1963- (John Wiley & Sons, 2020)
Blockchain is about to upend the world of data analytics just as it did financial record-keeping. Here's what you need to become an early adopted of blockchain as a big-data tool! Explore how blockchains store data and learn how this rich new source of data can enhance predictive analytics and real-time data analysis. You'll also find out how blockchains can help you manage your data and keep shared data more secure. Learn to implement blockchain analysis models, use third-party toolsets, assess your analysis needs, and more. -- From publisher's description.
Online resource; title from digital title page (viewed on September 18, 2020)
Keywords: Blockchains (Databases); Chaînes de blocs; COMPUTERS; Data Science; Data Modeling & Design; handbooks; Handbooks and manuals; Guides et manuels; Handbook